Meta-Analisis : Penelitian Penerapan Model Pembelajaran Inkuiri dengan Penguasaan Kompetensi Literasi Sains Peserta Didik pada Pembelajaran Fisika (Universitas Negeri Surabaya, 2023)
Inquiry learning models are often applied to physics study research to improve scientific literacy ability. The purpose of this research is to analyze what has been done about the inquiry learning model’s aplication to improve scientific literacy competency. This research methods use meta-analysis divided in to 4 stage such as : data collection, data reduction, data presentation, and a withdrawal of conclusions or verification. The data used in this research is a secondary of 20 proscriptions and a national and international journal article that was published in around of 7 years (2015-2021) on Google scholar. This research’s first step is to collect articles, then select 20 articles that have the same research design, create vosviewer software visualization, and calculate an effect size based on years of research, a level of education, learning materials and inquiry models. Based on the meta-analysis of 20 articles, it shows that inquiry learning models have a positive effect on the increased students’ scientific literacy indicated by the strong effect category. The research related to the effects of inquiry learning model of science was conducted largely in 2019-2020 high school, in static fluid material, global warming and Newton's law and guided inquiry. The most powerful effect size result is on high-school research, dynamic electrical materials and using guided inquiry Keywords: Inquiry, Learning Physics, and Science Literacy Ability